Advancing a global transition to clean energy: The role of international cooperation - Rainer Quitzow; Sonja Thielges; Andreas Goldthau; Sebastian Helgenberger; Grace Mbungu (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
International cooperation in support of a global energy transition is on the rise, and official development assistance (ODA) in the energy sector is increasingly being directed to renewable energy sources. Nevertheless, it is widely acknowledged that investment towards achieving the SDG 7 on clean and affordable energy is insufficient. Moreover, investment in clean energy remains heavily concentrated in a small number of frontrunner countries and overwhelmingly targets grid-connected electricity generation. Worryingly, significant share of international public sector financeing, most notably by export-credit agencies, is still allocated to coal and other fossil-based technologies. Against this background, this paper makes three recommendations for strengthening international cooperation in support of a global energy transition. (1) Promote investment in clean energy and end support for coal-based energy infrastructure. OECD and G20 countries should lead the way by discontinuing all public investment support for new coal-based energy infrastructure and establish guidelines for support to other fossil-based investments. (2) Promote evidence-policy dialogue on the socio-economic dimension of the global energy transition. International cooperation should play an active role in mobilising socio-economic benefits and address potential risks by supporting evidence-based policy dialogue based on robust assessments at both the country and global levels. (3) Provide early market support to promote challenge-based energy innovation. SE4ALL or Mission Innovation should create multi-stakeholder, challenge-based initiatives to promote clean energy innovation in developing and emerging economies and foster early market demand for related products or services.
Keywords: O12; O13; Q38; 330; public policy; climate; energy; innovation; development; international Political Economy